The Chinese Brief Cognitive Test: Normative Data Stratified by Gender, Age and Education - Ye, Shuling; Xie, Mengjuan; Yu, Xin; Wu, Renrong; Liu, Dengtang; Hu, Shaohua; Xu, Yong; Liu, Huanzhong; Wang, Xijin; Zhu, Gang; Wang, Huaning; Zou, Shaohong; et al. (Frontiers in Psychiatry, 2022)
The aim of this study was to develop a brief version of cognitive assessment test for evaluating the efficacy of treatments targeting cognitive impairments in Chinese schizophrenia patients, to examine its reliability, and establish normative data. Stratified according to age, gender, and educational level, healthy adult subjects were recruited from fifteen institutions in seven administrative regions of China and 723 valid samples were obtained, of which 50 were retested. Generalized Linear Models were conducted to analyze the effects of age, sex, and education. There was no significant difference between genders, while significant effects were demonstrated respectively among age and education on the normative data of C-BCT. The Cronbach α of C-BCT is 0.75, and the test-retest reliability (ICC) ranged from 0.62 to 0.76. Normative data of C-BCT were generated by gender, age and education, and the effects of these demographic factors were analyzed. It revealed good internal consistency and test-retest reliability of C-BCT.